PHONOLOGICAL PROCESSES AND ADAPTION CROSS LINGUISTIC EXAMINATION: A SYSTEMATIC LITERATURE REVIEW - Melani S, Rhosa (ELite Journal : International Journal of Education, Language and Literature, 2026)
The primary objective of this study is to examine phonological processes and adaptations across various languages, focusing on their influence on language acquisition, literacy development, and second language learning. The research spans from 2019 to 2024, covering recent studies in the field. Databases such as Google Scholar and Crossref were used for the initial search, utilizing tools like Zotero and Publish or Perish. Keywords such as "phonological processes," "language adaptation," "phonological awareness," and "cross-linguistic studies" were employed." A comprehensive search across major databases, including Crossref and Google Scholar, yielded an initial 1,200 articles. Rigorous inclusion and exclusion criteria were applied, including the removal of duplicates and non-English articles, resulting in 22 articles selected for in-depth analysis. The research synthesizes findings from multiple studies to provide a comprehensive understanding of the topic. Key findings highlight that phonological awareness instruction positively impacts engagement and outcomes in language learning, especially for young learners and those learning a second language. Systematic and explicit instruction in phonological awareness has been shown to significantly improve vocabulary acquisition and speaking skills. Future research should continue exploring the most effective methods for teaching phonological awareness in diverse linguistic contexts, ensuring that all learners have the opportunity to develop strong language skills. By addressing these areas, future studies can contribute to refining educational strategies, making phonological awareness instruction more adaptable and impactful across different learning environments.